2014
DOI: 10.1530/eje-14-0006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone on markers of mitochondrial oxidative phosphorylation and lipid metabolism in muscle of aging men with subnormal bioavailable testosterone

Abstract: Objective: Recent studies have indicated that serum testosterone in aging men is associated with insulin sensitivity and expression of genes involved in oxidative phosphorylation (OxPhos), and that testosterone treatment increases lipid oxidation. Herein, we investigated the effect of testosterone therapy on regulators of mitochondrial biogenesis and markers of OxPhos and lipid metabolism in the skeletal muscle of aging men with subnormal bioavailable testosterone levels. Methods: Skeletal muscle biopsies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
4
19
1
Order By: Relevance
“…Study in human muscle biopsy following testosterone therapy indicated that Ppia, Polymerase (RNA) II Subunit A (POLR2A) and Importin 8 (IPO8) were identified as suitable RG [20]. Even though HPRT is a variable gene among the examined set of genes under the influence of testosterone, unpublished data from our lab have identified GAPDH and HPRT as suitable RG in the uterus under the influence of estradiol in mature WKY rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study in human muscle biopsy following testosterone therapy indicated that Ppia, Polymerase (RNA) II Subunit A (POLR2A) and Importin 8 (IPO8) were identified as suitable RG [20]. Even though HPRT is a variable gene among the examined set of genes under the influence of testosterone, unpublished data from our lab have identified GAPDH and HPRT as suitable RG in the uterus under the influence of estradiol in mature WKY rat.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of some housekeeping genes [9,17], such as tubulin, cyclophilin, tyrosine aminotransferase, ACTB, GAPDH and 18S in the liver of intact female and male rats, was shown to be sex-dependent as their levels of expression were different in both genders [18]. In a study by Cai et al [19] ACTB was used as a RGs following castration in pig, whilst in another study in aging men Polymerase (RNA) II Subunit A (POLR2A), Importin 8 (IPO8) and Ppia were identified as suitable genes for data analysis in biopsies of skeletal muscle following testosterone therapy [20]. There was no study to report of expression of housekeeping genes under the influence of testosterone in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The largest difference in gene expression between normal and diabetic muscle was ubiquinol cytochrome c reductase binding protein that plays a critical role in OxPhos, and this expression was correlated with testosterone and insulin resistance . Testosterone replacement for 6 months in men with subnormal bioavailable testosterone levels increased lipid oxidation in muscle biopsies, although the expression of mitochondrial OxPhos genes was not altered . TRT in men with low free testosterone leads to an increase in lipid oxidation and a decrease in glucose oxidation, suggesting a shift in substrate partitioning to favour lipid utilization .…”
Section: Testosterone Mechanisms In Obesitymentioning
confidence: 96%
“…Usui et al (28) demonstrated that in mice, testosterone treatment resulted in an increase in heat production that the authors concluded was derived from elevated mitochondrial biogenesis in skeletal muscle. On the other hand, in hypogonadal men treated with testosterone, Petersson et al (19) observed no effect on insulin sensitivity or skeletal muscle mRNA levels of genes involved in mitochondrial biogenesis, oxidative phosphorylation, or lipid metabolism. We observed a small but significant increase in muscle mitochondrial protein FSR.…”
Section: E414 Fractional Synthesis Rates Of Skeletal Muscle Proteinsmentioning
confidence: 99%